PP.38.08: IMPAIRED BAROREFLEX FUNCTION IS RELATED TO REDUCED CAROTID ARTERY ELASTICITY IN PATIENTS WITH TETRALOGY OF FALLOT. (June 2015) - Pinter, A.; Horvath, T.; Toth, A.; Kadar, K.; Kollai, M.
Abstract : Objective: Sudden cardiac death (SCD) is a common late complication in patients with tetralogy of Fallot (ToF). Reduced baroreflex sensitivity (BRS) is an independent predictor of SCD and BRS reduction was reported in ToF. Relationship between BRS and carotid artery distensibility (DC) in healthy subjects was reported by us earlier. We also found that DC was reduced in ToF patients. In the present study we tested the hypothesis that reduced BRS is related to increased carotid artery stiffness. Design and method: We studied 36 ToF patients (21 ± 11 yrs.) and 60 age-matched healthy control subjects. Intravenous phenylephrine-induced (BRSphe) and spontaneous (BRSseq) BRS indices were derived. DC calculation was based on echo wall-tracking and tonometry. Results: BRS indices were reduced in patients compared with controls (BRSphe 16.8 ± 10.2 vs. 27.3 ± 9.2 ms/mmHg; BRSseq 9.3 ± 9.2 vs. 18.3 ± 7.8 ms/mmHg). DC was also lower in patients (5.1 ± 1.8 vs. 6.3 ± 2.6 10–3/mmHg). BRS correlated with DC across patients and controls (BRSphe r = 0.75 vs. r = 0.74; BRSseq r = 0.44 vs. r = 0.38). Multiple regression analysis indicated BRS indices are determined independently by DC in ToF patients. Conclusions: We showed that reduced DC may contribute to impaired baroreflex function in ToF patients and could in part explain the elevated risk for SCD postoperatively. Therefore it would be an important future investigation to test carotid artery stiffness and analyze its predictive value for cardiac mortality in ToF. Preventive actions to impede carotid artery stiffening should receive more attention in the clinical management of ToF patients.